Strategi Pengelolaan Berkelanjutan Perkebunan Kelapa Sawit Berdasarkan Analisis Degradasi Lingkungan di Kecamatan Tualang, Riau - Nengsih Elfianti; Dedi Hermon (Jurnal Penelitian Pendidikan IPA, 2026)
Land-use conversion from forests to oil palm plantations in Tualang District, Siak Regency, has intensified environmental and settlement pressures, requiring systematic evaluation. This study aims to analyse the spatial dynamics of forest conversion, assess environmental and settlement impacts, and formulate sustainable management strategies. A mixed-methods approach was employed, integrating spatial analysis of Landsat and Sentinel imagery, field surveys, observations, and in-depth interviews. Spatial change analysis and SWOT analysis were applied to interpret land-use dynamics and management options. The results indicate that from 2015 to 2025, oil palm expansion increased markedly, with forest and peatland conversion accounting for more than one-quarter of the total area. These changes led to soil degradation, biodiversity loss, increased runoff, water contamination, and reduced community access to natural resources. The proposed strategies emphasize conserving ecological buffers, strengthening community monitoring capacity, enforcing land-use regulations, and promoting sustainable plantation practices. Overall, integrated spatial planning and community participation are essential to ensure environmentally sustainable oil palm development.